Modeling and simulation of passive and active solar thermal systems - Candanedo, Luis Miguel; Athienitis, Andreas K.; Kalogirou, Soteris A.; Candanedo, Luis Miguel (My University, 2012)
This chapter presents major passive solar technologies and systems, followed by in-depth sections on their modeling using both analytical and numerical models. Next, more recent developments are described with a focus on building-integrated photovoltaic/thermal systems and net-zero energy solar homes that combine passive and active systems to produce as much energy from sunlight as they consume in an average year. The proper sizing of the components of an active solar system is a complex problem that includes both predictable and unpredictable parameters. Predictable parameters are related to the performance characteristics of the collector and other components, and the unpredictable parameters mainly concern weather data (solar radiation, ambient temperature, wind speed, and direction). In the second part of this chapter, various design methods are presented as well as an overview of the simulation techniques and programs suitable for active solar heating and cooling systems. The design methods presented include the f-chart and utilizability methods. For more detailed results, modeling and simulation is used. The software programs described briefly in this chapter include F-chart, TRNSYS, and WATSUN.
Keywords: Active solar heating; Analytical and numerical models; Building Integrated Photovoltaic/Thermal systems; F-chart method; Modeling; Net-zero energy solar buildings; Passive solar heating; Simulation software; Utilizability method